A fundamental assessment of the impacts of cation (Cd, Co, Fe) substitution on the molecular chemistry and surface reactivity of sphalerite. (1st January 2021) - Babedi, L.; Tadie, M.; Neethling, P.; von der Heyden, B.P.
Highlights: Cation substitutions affect sphalerite bulk-, surface- and flotability properties. The nature of metal impurity-sulphur bond in sphalerite affects Cu activation. Chemical nature of metal impurities affects the pH range of sphalerite flotation. Impurity induced changes in electronic properties of sphalerite influence collector speciation. Abstract: A series of cadmium-, cobalt-, and iron-substituted (0–4 wt%) sphalerite mineral samples were synthesised to test how the presence of these cation substituents alter the crystal structure, surface bonding environment and electronic properties of sphalerite and to illustrate how these alterations impact the electrokinetic behaviour of mineral surfaces under conditions relevant to sphalerite flotation. A combination of X-ray Diffraction (XRD), Raman and ultraviolet–visible spectroscopies, and zeta potential experiments were used to demonstrate these impacts. XRD results showed a positive correlation between the measured lattice distortions and the ionic size and concentration of the respective cation substituents. Raman results confirmed the presence of new metal-sulphur (M−S) bonds within the ZnS host cluster reflected by a new impurity mode which correlates to the concentration and chemical nature of the cation substituents. The presence of metal substituents further induced a change in the band gap of sphalerite which reduced according to Cd > Fe > Co. These measurements informed the effect of the molecular characteristics of impurity-bearing sphalerite on the electrokinetic response of sphalerite in the presence of CuSO4 and xanthate collector. Cobalt-bearing sphalerites which have the lowest band gap and greatest distortions to molecular and crystal structure had the most notable impact on zeta potential measurements. A small increase in Co concentration induced a larger shift in point of zero charge for collectorless activation but did not impact the collector interactions. Conversely, Cd which has a wider band gap is less electronegative than Co exhibited the reverse behaviour. This study thus details how the presence of cation substituents modifies sphalerite bulk structure, in turn impacting its surface bonding environment and electronic properties, and ultimately exerting a notable control on flotation chemistry.